2007
DOI: 10.1007/s11434-007-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

Modern stalagmite oxygen isotopic composition and its implications of climatic change from a high-elevation cave in the eastern Qinghai-Tibet Plateau over the past 50 years

Abstract: An oxygen isotope record of a stalagmite from Huanglong Cave in the eastern Qinghai-TibetPlateau dated with 230 Th and 210 Pb methods provides variations of the Asian monsoon with an average resolution of 1 year over the past 50 years. This study shows that the δ 18 O of dripwater in the cave represents the annual mean δ 18 O of local meteoric precipitation and the stalagmites were deposited in isotopic equilibrium. A comparison of the stalagmite δ 18 O record with instrumentally meteorological data indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…High-resolution subsampling was conducted using the dental drill and graver [25]. First, two 10-mm parallel lines along the growth axis were drawn on the polished stalagmite section.…”
Section: High-resolution Subsamplingmentioning
confidence: 99%
“…High-resolution subsampling was conducted using the dental drill and graver [25]. First, two 10-mm parallel lines along the growth axis were drawn on the polished stalagmite section.…”
Section: High-resolution Subsamplingmentioning
confidence: 99%
“…Many significant results have been obtained on the variation and strength of AM [7][8][9][10][11]13,14] and the relationship between the AM and solar insolation on glacial/interglacial, millennial and centennial timescales using stalagmites [7][8][9]11,[13][14][15][16] . In particular, it was recently found that the stalagmite oxygen isotopic composition (δ 18 O) of stalagmite calcite could record interannual variation of the AM [17] and some historical severe famine events in tropics and subtropics [18] that corresponded to a weakening of the AM. Moreover, that the monsoonal precipitation was strongly linked to ocean-atmosphere systems in the Pacific Ocean and the North Atlantic Ocean, e.g., PDO, El Niño/Southern Oscillation (ENSO) [15] and North Atlantic Oscillation [19] .…”
mentioning
confidence: 99%
“…However, the trends of extreme wet events among the stations over the SC are unremarkable in the 2000s compared with the other decades (Fig. 4), which can likewise be attributed to the weak southwest monsoon (Fleitmann et al, 2004;He et al, 2005;Yang et al, 2007). During the summer and winter monsoon period (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…These changes are abnormal, and can be attributed to the weakening of the Asian monsoon circulation (Li et al, 2012) and climate change (Trenberth et al, 2003;Groisman et al, 2005). In addition, many studies have demonstrated that the strength of the southwest monsoon has gradually weakened for nearly half a century in China (Fleitmann et al, 2004;He et al, 2005;Yang et al, 2007), which can further explain the results.…”
Section: Discussionmentioning
confidence: 93%